An Overview of Continuing Medical Education/Continuing Professional Development Systems in the Middle East and North Africa: A Mixed Methods Assessment - Lawrence Sherman; Samar Aboulsoud; Kathy Chappell (Journal of CME)
The aims of this assessment were to describe the requirements for physicians to engage in CME/CPD; explore perceptions of in-country SMEs of their CME/CPD systems; describe perceptions of in-country physicians about interprofessional continuing education (IPCE) and independent CME/CPD; and provide recommendations that may be adopted to improve quality and effectiveness. An assessment of CME/CPD systems in the Middle East and North Africa was conducted using a mixed-methods approach that included 1:1 interviews with in-country SMEs and an electronic survey capturing qualitative and quantitative data from practicing in-country physicians. The results of this assessment were strongly influenced by Egypt and Israel in the Middle East, and Algeria and Morocco in North Africa. The CME/CPD systems demonstrate wide variation from absent/immature systems to robust/mature systems. Strategies to improve the quality of the CME/CPD systems range from implementing basic standards in North Africa to evaluating the impact of CME/CPD in practice in the Middle East. The maturity of CME/CPD systems seems to affect physician awareness, independence from the influence of pharmaceutical companies over education, and IPCE, with more mature systems having a positive relationship to awareness, independence and engagement in IPCE. Maturity of CME/CPD systems is less tied to physician perceptions of value of CME/CPD, hours of participation, perceptions of what is missing from current systems, and preferred formats of education.